Equi-biaxial loading effect on austenitic stainless steel fatigue life (Fracture and Structural Integrity, 2016)
Fatigue lifetime assessment is essential in the design of structures. Under-estimated predictions may result in unnecessary in service inspections. Conversely, over-estimated predictions may have serious consequences on the integrity of structures. In some nuclear power plant components, the fatigue loading may be equibiaxial because of thermal fatigue. So the potential impact of multiaxial loading on the fatigue life of components is a major concern. Meanwhile, few experimental data are available on austenitic stainless steels. It is essential to improve the fatigue assessment methodologies to take into account the potential equi-biaxial fatigue damage. Hence this requires obtaining experimental data on the considered material with a strain tensor in equibiaxial tension. Two calibration tests (with strain gauges and image correlation) were used to obtain the relationship between the imposed deflection and the radial strain on the FABIME2 specimen. A numerical study has confirmed this relationship. Biaxial fatigue tests are carried out on two austenitic stainless steels for different values of the maximum deflection, and with a load ratio equal to -1. The interpretation of the experimental results requires the use of an appropriate definition of strain equivalent. In nuclear industry, two kinds of definition are used: von Mises and TRESCA strain equivalent. These results have permitted to estimate the impact of the equibiaxiality on the fatigue life of components.
Keywords: Design fatigue curve; Equibiaxiality; Experimental device; Austenitic steel